Combining extensive reading while listening (ERWL) with cooperative learning - Tsuda, Kaoru; Muramatsu, Noriko; Renandya, Willy A; Jacobs, George M (JOALL (Journal of Applied Linguistics and Literature), 2023)
In this teaching-oriented project, we propose an extensive reading while listening (ERWL) program in which cooperative learning (CL) tasks are also implemented. We believe that by implementing ERWL combined with CL tasks, teachers can invite their learners to improve all four language skills while simultaneously enhancing their motivation for ERWL. We will first explain the benefits of ERWL and CL for second language (L2) learners and then the rationale for combining these two learning methods. Next, we will present CL tasks designed for students to improve all four language skills while doing ERWL.